Improving the design of a residential building using the Portuguese rating system SBToolPT - Bragança, L. (2011)
Construction affects all dimensions of sustainability (environment, society and economy) and therefore a sustainable building design has to cope with tens of criteria, most of them interrelated and partly contradictory. There are a great number of indicators and assessment tools that have been developed recently in order to evaluate the sustainability of buildings and urban settlements. Most of these tools are based on national standards, building codes and local methods of construction. Sustainable design of construction is only possible through a real methodological work. Sustainability assessment tools play an important role at this level, since they convert the sustainability issues into tangible goals while are used to collect and communicate the results of a sustainability assessment. This paper will present the role of the Portuguese Sustainability Rating System SBToolPT in promoting the sustainability of residential buildings.